(untitled) (Research, Society and Development, 2022)
Prenatal care, in addition to monitoring risk factors and treating complications, aims to promote the health of pregnant women and the fetus, and should be performed by the end of pregnancy. Thus, the presence of the father in prenatal care brings benefits to maternal and child health. The aim of this study was to describe the importance of paternal presence in prenatal care and to highlight the benefits that this follow-up brings to the pregnant woman and consequently to the baby. Therefore, an integrative review was performed in 2 databases: BVS and SciELO using boolean and OR operators. It is noteworthy that the paternal presence in prenatal consultations is still low, implying the failure of the father to not be able to assume and accept responsibility as it should. For the father to better fulfill the prenatal strategy of his partners, new policies are still needed that expand the right of men to participate in this time of pregnancy. Thus, it is concluded that, despite these limitations, the participation of the father in pregnancy and childbirth is significant and is under construction. Nurses represent a necessary element for greater male support and involvement in this process, and play a crucial role, as they should be the main motivators and encouragers in the involvement of men in prenatal care to benefit the mother-father-child triad. Future research is needed to consider the diverse levels of health care that may contribute to accountability, autonomy, empowerment and paternal esteem during pregnancy, childbirth and postpartum.